Preparation method of high-compaction lithium iron phosphate positive electrode material

CN122977345APending Publication Date: 2026-10-27锂源(深圳)科学研究有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611463469.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

而这些制备方法,存在生产成本高、生产稳定性差、磁性杂质含量高、倍率性能差的问题,最终影响到超高压实磷酸铁锂的产品的大面积应用

Benefits of technology

[0024]有益效果:与现有技术相比,本发明的显著优点为,

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977345A_ABST
    Figure CN122977345A_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing high-compact lithium iron phosphate (LFP) cathode material. First, low-carbon, large-particle-size LFP particles doped with a first titanium source are prepared. Based on these large-particle-size LFP particles, they are mixed with a lithium source, a second titanium source, a phosphorus source, and a carbon source, and then milled with water to prepare a second slurry. Next, an iron source, lithium source, phosphorus source, carbon source, and anatase titanium dioxide are mixed with water and milled to prepare a third slurry. Then, a third titanium source is added, and the mixture is milled again to obtain a fourth slurry. Finally, the second and fourth slurries are mixed and stirred, and then spray-dried, sintered, and subjected to airflow milling to obtain the high-compact LFP cathode material. The LFP cathode material prepared by this method achieves a compaction density of 2.7 g / cm³. 3 It has high compaction properties and excellent electrochemical performance, achieving simultaneous improvement in compaction and electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium iron phosphate cathode material preparation technology, and particularly relates to a method for preparing high-pressure lithium iron phosphate cathode material. Background Technology

[0002] Lithium iron phosphate (LiFePO4) has become a core cathode material for power batteries and energy storage batteries due to its advantages of high safety, long cycle life, and low cost. With the continuous increase in energy density requirements of the new energy industry, improving the compaction density of LiFePO4 has become a key technological direction—every 0.1 g / cm³ increase in compaction density can increase the volumetric energy density of the battery by approximately 5%-8%. Currently, conventional methods for preparing high-compaction LiFePO4 include particle gradation methods, such as preparing precursors with different milling particle sizes for mixing and gradation, using different sintering processes to prepare LiFePO4 with different particle sizes, followed by finished product mixing and gradation, or milling and grading first-burned materials of different sizes before secondary sintering, and grading multiple different precursors. All of these methods require the introduction of a gradation process, increasing preparation costs. Furthermore, the diversity of precursors also places higher demands on product consistency.

[0003] Furthermore, in existing technologies, to achieve a higher compaction density of 2.7 g / cm³ or above, multi-stage gradation with three or more different particle sizes is often used, or higher sintering temperatures are employed. However, these preparation methods suffer from high production costs, poor production stability, high magnetic impurity content, and poor rate performance, ultimately affecting the widespread application of ultra-high compaction lithium iron phosphate products.

[0004] Based on this, a high-compaction method for preparing lithium iron phosphate is proposed. This method abandons the traditional approach of using at least three different particle sizes for multi-stage gradation or employing higher sintering temperatures, while still achieving a powder compaction of up to 2.7 g / cm³. 3 The above describes lithium iron phosphate cathode materials that possess both good rate capability and good safety performance. Summary of the Invention

[0005] Objective of the invention: This invention provides a novel preparation process for lithium iron phosphate cathode materials, enabling the achievement of a compaction density of up to 2.7 g / cm³. 3 The above describes a lithium iron phosphate cathode material that simultaneously possesses good rate capability and safety performance, achieving a simultaneous improvement in compaction and electrochemical performance.

[0006] Technical solution: The present invention provides a method for preparing high-pressure lithium iron phosphate cathode material, comprising the following steps:

[0007] (1) The phosphorus source, iron source, lithium source, carbon source and first titanium source are mixed with water and prepared into a first slurry by sand milling. The first slurry is then spray-dried, sintered and air-crushed to D50≥2um to obtain large-size lithium iron phosphate particles.

[0008] (2) The large-particle-size lithium iron phosphate particles, lithium source, second titanium source, phosphorus source and carbon source are mixed with water and prepared into a second slurry by sand milling;

[0009] (3) The phosphorus source, iron source, lithium source, carbon source and anatase titanium dioxide are mixed with water and prepared into a third slurry by sand milling. Then, a third titanium source is added and sand milled to obtain a fourth slurry. The third titanium source is selected from tetrabutyl titanate, titanium isopropoxide or rutile titanium dioxide, and its addition amount is 0.01%-0.5% of the theoretical amount of lithium iron phosphate generated in this step.

[0010] (4) The second slurry and the fourth slurry are mixed and stirred at a mass ratio of (0.5-1.5):1, and then spray-dried, sintered and air-jet pulverized to obtain high-pressure lithium iron phosphate cathode material.

[0011] Furthermore, in the preparation method of the present invention, the first titanium source and the second titanium source are both selected from at least one of anatase titanium dioxide, tetrabutyl titanate, titanium isopropoxide, titanium chloride or titanium sulfate, and the amount of the first titanium source added is 0.05%-0.5% of the theoretical amount of lithium iron phosphate generated in step (1).

[0012] Furthermore, the phosphorus source used in the preparation method of the present invention is selected from one or more of ferric phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate;

[0013] The iron source is selected from one or more of ferric phosphate, ferrous oxalate, ferric oxide, and iron(II,III) oxide.

[0014] The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate.

[0015] The carbon source is selected from one or more of glucose, sucrose, citric acid, polyethylene glycol, and polyvinylpyrrolidone.

[0016] Furthermore, in step (1) of the preparation method of the present invention, the molar ratio of Li, P and Fe in the lithium source, phosphorus source and iron source is (1.0-1.05):1:(0.95-0.98).

[0017] Furthermore, in step (2) of the preparation method of the present invention, the amount of lithium source, second titanium source and phosphorus source added is such that the mass of theoretically generated lithium titanium phosphate accounts for 0.01%-2% of the mass of large-diameter lithium iron phosphate particles.

[0018] Furthermore, in step (3) of the preparation method of the present invention, the molar ratio of Li, P and Fe in the lithium source, phosphorus source and iron source is (1.0-1.05):1:(0.95-0.98).

[0019] Furthermore, in step (3) of the preparation method of the present invention, the amount of anatase titanium dioxide added is 0.05%-0.8% of the theoretical amount of lithium iron phosphate generated in this step.

[0020] Furthermore, in step (1) of the preparation method of the present invention, the amount of carbon source added is 4-10% of the theoretical amount of lithium iron phosphate generated in this step;

[0021] In step (2), the amount of carbon source added is 4-6% of the mass of the large-diameter lithium iron phosphate particles;

[0022] In step (3), the amount of carbon source added is 4-10% of the theoretical amount of lithium iron phosphate generated in this step.

[0023] Furthermore, in step (1) of the preparation method of the present invention, the sintering temperature is 650-790℃; in step (4), the sintering temperature is 700-750℃.

[0024] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are,

[0025] (1) The compaction density of the lithium iron phosphate cathode material prepared by this method can reach 2.7 g / cm³. 3 and above, possessing high compaction properties;

[0026] (2) The lithium iron phosphate cathode material prepared by this preparation method has a powder resistivity of less than 14 Ω·cm, a 0.1C discharge capacity of more than 158 mAh / g, and a 1C discharge capacity of more than 142 mAh / g, and has excellent electrochemical performance.

[0027] The lithium iron phosphate cathode material prepared by this method achieves simultaneous improvement in compaction and electrochemical performance. Attached Figure Description

[0028] Figure 1 This is an electron microscope image of the lithium iron phosphate cathode material prepared in Example 1 of the present invention;

[0029] Figure 2 This is an electron microscope image of the lithium iron phosphate cathode material prepared in Example 2 of the present invention. Detailed Implementation

[0030] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0031] It should be noted that the theoretical production amount of lithium iron phosphate involved in this invention is the theoretical mass of lithium iron phosphate produced by the reaction of iron source, phosphorus source and lithium source, and includes 1.3% theoretical residual carbon content.

[0032] Example 1

[0033] The lithium iron phosphate cathode material of Example 1 was prepared by the following steps:

[0034] 1. Preparation of large-particle lithium iron phosphate cathode materials

[0035] 1) Select an iron-to-phosphorus ratio of 0.9676 and a specific surface area of ​​7.284 m². 2 For a given ferric phosphate concentration of / g, weigh out 4000g ferric phosphate, 997.00g lithium carbonate, 20g anatase titanium dioxide, and 240g glucose as a carbon source.

[0036] 2) Iron phosphate, lithium carbonate, anatase titanium dioxide and glucose are mixed with water at a solid content of 40% and stirred evenly. The mixture is then milled to a D50 of 0.500±0.005um to obtain the first slurry.

[0037] 3) The first slurry was dried under the conditions of spray drying inlet air temperature of 200-280℃, outlet air temperature of 80-90℃, and atomizer speed of 21000rpm to obtain dried material;

[0038] 4) The dried material was sintered at 775°C for 8 hours under an inert atmosphere and then air-crushed to obtain low-carbon, large-particle-size lithium iron phosphate particles with D50≥2um.

[0039] 2. Preparation of large-particle lithium iron phosphate cathode material slurry

[0040] 1) Take 3 kg of the above low-carbon, large-particle-size lithium iron phosphate particles, 100 g of PEG-4K, 30 g of PVP, 1.430 g of lithium carbonate, 6.182 g of anatase titanium dioxide, and 13.356 g of ammonium dihydrogen phosphate.

[0041] 2) Add low-carbon, large-particle-size lithium iron phosphate particles, lithium carbonate, anatase titanium dioxide, ammonium dihydrogen phosphate, and glucose to deionized water in sequence according to a solid content of 40%. Stir evenly and coarsely grind with 0.6-0.7um zirconium beads to D50=1.5um to obtain the second slurry.

[0042] 3. Preparation of small-particle lithium iron phosphate cathode material slurry

[0043] 1) Select the same iron phosphate as used for preparing large-particle lithium iron phosphate, weigh 3000g iron phosphate, 757.50g lithium carbonate, 23.120g anatase titanium dioxide and 14.997g tetrabutyl titanate as composite titanium source, and 75g PEG-4K and 165g glucose as carbon source.

[0044] 2) Add iron phosphate, lithium carbonate, anatase titanium dioxide, PEG-4K and glucose to deionized water at a solid content of 40%, and grind it to 0.40 μm with 0.3 μm zirconium beads to obtain the third slurry; add tetrabutyl titanate to the third slurry, and continue grinding to 0.35 μm to obtain the fourth slurry.

[0045] 4. Preparation of high-compact, high-electrochemical-performance lithium iron phosphate cathode materials

[0046] The second and fourth slurries were mixed evenly at a mass ratio of 1:1, and then spray-dried under the conditions of inlet air temperature of 200-280℃, outlet air temperature of 80-90℃, and atomizer speed of 21000rpm to obtain dried material. The dried material was then sintered at 720℃ in an inert atmosphere for 8 hours, and after cooling, lithium iron phosphate cathode material was obtained.

[0047] Example 2

[0048] The lithium iron phosphate cathode material of Example 2 is prepared in a method that is basically the same as that of Example 1, except that the 14.997g of tetrabutyl titanate in Example 1 is replaced with 3.520g of rutile titanium dioxide.

[0049] Example 3

[0050] The lithium iron phosphate cathode material of Example 3 is prepared in a method that is basically the same as that of Example 1, except that 14.997g of tetrabutyl titanate is replaced with 12.524g of titanium isopropoxide.

[0051] Example 4

[0052] The lithium iron phosphate cathode material of Example 4 is prepared in a method that is basically the same as that of Example 1. The difference is that the iron phosphate in Example 1 is replaced with iron oxide red and ammonium dihydrogen phosphate in equal molar amounts of iron and phosphorus.

[0053] Comparative Example 1

[0054] Comparative Example 1 is basically the same as Example 1, except that anatase titanium dioxide is not added when preparing large-particle lithium iron phosphate cathode material slurry in step 2; and tetrabutyl titanate is not added when preparing small-particle lithium iron phosphate cathode material slurry in step 3.

[0055] Comparative Example 2

[0056] Comparative Example 2 is basically the same as Example 1, except that anatase titanium dioxide is not added when preparing the large-particle lithium iron phosphate cathode material slurry in step 2.

[0057] Comparative Example 3

[0058] Comparative Example 3 is basically the same as Example 1, except that tetrabutyl titanate is not added when preparing small-particle lithium iron phosphate cathode material slurry in step 3.

[0059] Comparative Example 4

[0060] Comparative Example 4 is basically the same as Example 1, except that in step 3, step 2), when preparing the small-particle lithium iron phosphate cathode material slurry, tetrabutyl titanate is directly mixed with iron phosphate, lithium carbonate, anatase titanium dioxide, PEG-4K, and glucose. The specific steps are as follows:

[0061] 2) Add ferric phosphate, lithium carbonate, tetrabutyl titanate, anatase titanium dioxide, PEG-4K and glucose to deionized water at a solid content of 40%, and then grind the mixture to 0.35 μm with 0.3 μm zirconium beads to obtain the third slurry.

[0062] 4. Preparation of high-compact, high-electrochemical-performance lithium iron phosphate cathode materials

[0063] The second and third slurries were mixed evenly at a mass ratio of 1:1, and then spray-dried under the conditions of inlet air temperature of 200-280℃, outlet air temperature of 80-90℃, and atomizer speed of 21000rpm to obtain dried material. The dried material was then sintered at 720℃ in an inert atmosphere for 8 hours, and after cooling, lithium iron phosphate cathode material was obtained.

[0064] Performance testing

[0065] The cathode materials prepared in the above examples and comparative examples were compacted and their electrochemical performance was tested. The results are shown in Table 1 below.

[0066] Table 1. Compacted density and rate performance of lithium iron phosphate

[0067]

[0068] As shown in the table, the compacted density of lithium iron phosphate prepared in the embodiments of the present invention can reach 2.7 g / cm³. 3 At the same time, the powder resistivity is less than 14 Ω·cm, the 0.1C discharge capacity can reach more than 158 mAh / g, and the 1C discharge capacity can reach more than 142 mAh / g, achieving simultaneous improvement in compaction and electrochemical performance, breaking the drawback of mutual restriction of performance.

[0069] Based on the results of this experiment, combined with Figure 1 and Figure 2Further analysis of the mechanism reveals that this invention first prepares large-particle lithium iron phosphate cathode material and then constructs a fast-ion conductor coating layer of lithium titanium phosphate generated by the reaction of titanium, lithium, and phosphorus sources on its surface. This improves the compaction of the large-particle lithium iron phosphate cathode material, and simultaneously promotes the insertion / extraction of large lithium ions through the fast-ion conductor coating layer, thereby increasing its ion migration rate and improving its charge / discharge capacity at high rates. Building upon this improved electrochemical performance of the large-particle lithium iron phosphate cathode material, a small-particle lithium iron phosphate cathode material slurry is prepared. During the preparation of the small-particle lithium iron phosphate cathode material slurry, a titanium source capable of forming surface doping is added. Through the synergy between the surface titanium source and the carbon coating layer, titanium-carbon bonding is promoted, thereby altering the growth direction of the carbon coating layer microcrystals. This ultimately yields small-particle lithium iron phosphate with a high degree of surface smoothness, making it easier for the small particles to fill the interior of the large particles. Figure 1 and Figure 2 The small particles filling the large particles further promote the simultaneous improvement of the material's compaction density and volume.

[0070] Further analysis of the data from Example 1 and Comparative Example 4 reveals that in Example 1, the preparation of small-particle lithium iron phosphate cathode material slurry involved first mixing and milling a mixture of phosphorus source, iron source, lithium source, carbon source, and anatase titanium dioxide before adding a third titanium source. In contrast, Comparative Example 4, which directly mixed and milled the phosphorus source, iron source, lithium source, carbon source, anatase titanium dioxide, and the third titanium source, showed a significant improvement in compaction. These experiments demonstrate that by first adding anatase titanium dioxide to form bulk doping, and then adding the third titanium source, the process adjustment effectively promotes the formation of the third titanium source primarily within the carbon coating layer, constituting surface doping. This facilitates the bonding between the third titanium source and the carbon source, altering the growth direction of graphite crystals. Ultimately, this results in small-particle lithium iron phosphate with a high degree of surface smoothness, allowing the small-particle lithium iron phosphate to more smoothly fill the voids in the large-particle lithium iron phosphate, reducing the specific surface area and improving compaction performance.

Claims

1. A method for preparing a high-pressure lithium iron phosphate cathode material, characterized in that, Includes the following steps: (1) The phosphorus source, iron source, lithium source, carbon source and first titanium source are mixed with water and prepared into a first slurry by sand milling. The first slurry is then spray-dried, sintered and air-crushed to D50≥2um to obtain large-size lithium iron phosphate particles. (2) The large-particle-size lithium iron phosphate particles, lithium source, second titanium source, phosphorus source and carbon source are mixed with water and prepared into a second slurry by sand milling; (3) The phosphorus source, iron source, lithium source, carbon source and anatase titanium dioxide are mixed with water and prepared into a third slurry by sand milling. Then, a third titanium source is added and sand milled to obtain a fourth slurry. The third titanium source is selected from tetrabutyl titanate, titanium isopropoxide or rutile titanium dioxide, and its addition amount is 0.01%-0.5% of the theoretical amount of lithium iron phosphate generated in this step. (4) The second slurry and the fourth slurry are mixed and stirred at a mass ratio of (0.5-1.5):1, and then spray-dried, sintered and air-jet pulverized to obtain high-pressure lithium iron phosphate cathode material.

2. The method for preparing the high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The first titanium source and the second titanium source are both selected from at least one of anatase titanium dioxide, tetrabutyl titanate, titanium isopropoxide, titanium chloride or titanium sulfate. The amount of the first titanium source added is 0.05%-0.5% of the theoretical amount of lithium iron phosphate generated in step (1).

3. The method for preparing the high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, The phosphorus source is selected from one or more of ferric phosphate, diammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; The iron source is selected from one or more of ferric phosphate, ferrous oxalate, ferric oxide, and iron(II,III) oxide. The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate. The carbon source is selected from one or more of glucose, sucrose, citric acid, polyethylene glycol, and polyvinylpyrrolidone.

4. The method for preparing the high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, In step (1), the molar ratio of Li, P and Fe in the lithium source, phosphorus source and iron source is (1.0-1.05):1:(0.95-0.98).

5. The method for preparing the high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, In step (2), the amount of lithium source, second titanium source and phosphorus source added is such that the mass of theoretically generated lithium titanium phosphate accounts for 0.01%-2% of the mass of large-diameter lithium iron phosphate particles.

6. The method for preparing the high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, In step (3), the molar ratio of Li, P and Fe in the lithium source, phosphorus source and iron source is (1.0-1.05):1:(0.95-0.98).

7. The method for preparing the high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, In step (3), the amount of anatase titanium dioxide added is 0.05%-0.8% of the theoretical amount of lithium iron phosphate generated in this step.

8. The method for preparing the high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, In step (1), the amount of carbon source added is 4-10% of the theoretical amount of lithium iron phosphate produced in this step; In step (2), the amount of carbon source added is 4-6% of the mass of the large-diameter lithium iron phosphate particles; In step (3), the amount of carbon source added is 4-10% of the theoretical amount of lithium iron phosphate generated in this step.

9. The method for preparing the high-pressure lithium iron phosphate cathode material according to claim 1, characterized in that, In step (1), the sintering temperature is 650-790℃; in step (4), the sintering temperature is 700-750℃.